Statistical assessment of ELM triggering by pellets on JET. (22nd February 2021) - Lennholm, M.; McKean, R.; Mooney, R.; Tvalashvili, G.; Artaserse, G.; Baruzzo, M.; Belonohy, E.; Calabro, G.; Carvalho, I.S.; Challis, C.D.; de la Luna, E.; Frigione, D.; et al.
Abstract: This article investigates the triggering of ELMs on JET by injection of frozen pellets of isotopes of Hydrogen. A method is established to determine the probability that a specific pellet triggers a particular ELM. This method allows clear distinction between pellet-ELM pairs that are very likely to represent triggering events and pairs that are very unlikely to represent such an event. Based on this, the pellet parameters that are most likely to affect the ability of pellets to trigger ELMs have been investigated. It has been found that the injection location is very important, with injection from the vertical high field side showing a much higher triggering efficiency than low field side (LFS) injection. The dependence on parameters such as pellet speed and size and the time since the last ELM is also seen to be much stronger for LFS injection. Finally, the paper illustrates how improvements to the pellet injection system by streamlining the pellet flight lines and slightly increasing the pellet size has resulted in a significantly improved ability to deliver pellets to the plasma and trigger ELMs.